An air handling unit fault isolation method by producing additional diagnostic information proactively. (February 2021) - Li, Tingting; Deng, Mengqiu; Zhao, Yang; Zhang, Xuejun; Zhang, Chaobo
Abstract: As summarized in ASHRAE project RP-1312, an air handling unit (AHU) might suffer from 31 types of faults. Among them, 11 types of faults are of the most serious. Due to the limitation of initial cost, AHUs are always equipped with a limited amount of sensors that are vital for the purpose of automatic control. The diagnostic information is very poor. Therefore, it is challenging to isolate these faults. In this study, a proactive AHU fault isolation method is proposed to overcome this problem. Its basic idea is to introduce dynamic disturbances to the faulty AHUs to produce additional diagnostic information. The dynamic disturbances are generated through proactive actions such as resetting set-points or control signals in building management systems or AHU controllers. A list of proactive fault isolation rules is proposed to isolate these serious faults based on the additional diagnostic information. Evaluations are made on a simulated variable air volume air-conditioning system. Results show that the proposed method can isolate the serious faults of AHUs effectively.